Trans sectoral care of geriatric cancer patients based on comprehensive geriatric assessment and patient-reported quality of life - results of a multicenter study to develop and pilot test a patient-centered interdisciplinary care concept for geriatric oncology patients (PIVOG) - Schmidt, Heike Birgit; Jordan, Karin (Journal of geriatric oncology, 2017)
Objectives: For older patients with cancer the maintenance of independence, functionality and health-related quality of life (HRQOL) is of great importance. Aiming to maintain HRQOL of older patients with cancer we developed an interdisciplinary care program based on comprehensive geriatric assessment (CGA) and patient-reported HRQOL comprising tailored supportive measures and telephone-based counseling during 6month aftercare. Materials and Methods: Pilote-testing of the intervention took place in three centers at the University Hospital Halle to examine feasibility, acceptance and potential benefit. Patients≥70years with confirmed diagnosis of cancer, at least one comorbidity and/or one functional impairment, receiving curative or palliative care were eligible. Primary endpoint was global HRQOL (EORTC QLQ C30). Results: Mean age of the participants (n=100) was 76.3years (SD 4.8), 47% were female. On average they had 5 comorbidities (SD 2.8, min. 0, max. 15) and took 8 prescribed medications (SD 3.6, min. 0, max. 15). According to predefined treatment pathways, supportive care was triggered by summarized individual assessments that were presented to the treating physicians. Descriptive analyses showed that global HRQOL measured at the 6-month follow-up (n=57) had declined (≥10 points) for n=16 (28%) and improved or remained unchanged for n=41 (72%) patients, although some functional scales (e.g. mobility, role function) and some symptoms (e.g. fatigue, pain) had worsened. The nurse-led telephone-based aftercare was well accepted. Conclusion: The results show feasibility and potential benefit of the combination of CGA and HRQOL to complement standard assessments. Patient-reported symptoms and functioning indicate the need for intensified supportive therapy during aftercare.